Optimization of anesthetic management of surgical treatment of colorectal cancer. Part III: clinical and morphological aspects - S. P. Novikov; L. A. Kirillova; P. S. Novikova; I. V. Tverdokhleb (Морфологія, 2018)
ABSTRACT. Background. Interest in the study of the properties of sevoflurane, increased in recent years due to its influence on hemodynamics and morphological condition of the respiratory department of lungs, causes advisability of analyzing the structure of organs directly involved in the reactions of radical surgery for colorectal cancer. Objective. The purpose of research is to select the optimal method of anesthesia protection of patients from operating aggression during surgical treatment of colorectal cancer, comparative analysis of tissue and cell ultrastructure in intraoperative biopsies of the colon in the conditions of application of the standard ataralgesia and combined anesthesia with epidural analgesia. Methods. It was performed a comparative analysis of clinical and morphological data and results of treatment using total intravenous anesthesia followed analgesia with opiates analgesics, and combined techniques using low-flow sevoflurane anesthesia and epidural analgesia, followed by prolonged epidural anesthesia. Results. It was shown a significant advantage of combined techniques in comparison with total intravenous anesthesia due to: normodynamic type of hemodynamics during operation, possibility to extubate patient in operating room, effective analgesia in early postoperative period. Methods of prolonged epidural analgesia provided a significant need reduction for opioid analgesics, efficient analgesia in postoperative period, saved anti-tumor immunity and resistance to metastasis in patients with cancer, has provided more early resumption of intestine motor function, reduced terms of patient's staying in the intensive care unit. Implemented methodology reduced the frequency of postoperative mortality, complications, average length of hospital stay and frequency of patient returns to intensive care unit. Combined low-flow sevoflurane inhalation anesthesia and epidural analgesia with bupivacaine during radical operations followed by containment of endothelial dysfunction by limiting the destructive and degenerative changes in the endothelial cell organelles, stabilization of membranes, preventing spasm of arterioles, stasis and erythrocyte sludge. Conclusion. Combined techniques of low-flow sevoflurane anesthesia and epidural analgesia, followed by prolonged epidural anesthesia is an optimal method of anesthesia protection of patients from operating aggression during surgical treatment of colorectal cancer. Methods of epidural analgesia versus opioid analgesia leads to a significant reduction of the phenomena of infiltration, perivascular and interstitial edema in the composition of the intestinal wall in the area of surgical procedure..